Early onset schizophrenia in a 17 year old child - Melati Indah Jelita; Tendry Septa (Sean Institute, 2024)
Schizophrenia is a serious mental disorder that can affect behavior, emotions, and communication. Schizophrenia sufferers can experience hallucinations, delusions, confused thinking, and changes in behavior that can be detected at an early age range of 16 or 17 years or generally can also occur at 16 or 17 years which is referred to as early onset. Case: The patient is a boy aged 17 years old The patient hit his biological father and there was a change in behavior since the end of April 2023 which was informed by the Islamic boarding school to the patient's parents. The patient believes he is close to Allah and can punish people who are deemed to have sinned. The patient admitted to hearing whispered voices in the form of commands or comments which influenced changes in the patient's behavior which also made him irritable. Discussion: The patient was diagnosed as suffering from paranoid schizophrenia. The patient had perception disorders in the form of auditory, visual, and tactile hallucinations and depersonalization. There is a disturbance in the form of non-realistic thought and there is a disturbance in the content of thought in the form of delusions of grandeur in the patient. The psychiatric approach for patients consists of administering atypical antipsychotics along with supportive psychotherapy. Psychoeducation and family therapy are also carried out to ensure that the patient's family understands the disease and the importance of compliance with treatment. Conclusion: Apart from requiring pharmacological therapy, patients with schizophrenia also need psychotherapy and psychoeducation so that patients receive family support and speed up the patient's recovery. Holistic care is needed to treat patients to prevent disease recurrence. Early-onset schizophrenia patients must have ongoing therapeutic monitoring because they can develop worse schizophrenia in later adulthood.